PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), dan DANA ALOKASI KHUSUS (DAK) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN/KOTA PROPINSI SULAWESI TENGAH PERIODE TAHUN 2010-2016 - Ardiyanti, Rina; Jokolelono, Eko; Sading, Yunus (Katalogis, 2019)
The purpose of this research is to know whether the Regional Real Income, General Allocation Fund, simultaneously affect the Gross Regional Domestic Product of Central Sulawesi Propince in the period of 2010-2016 and the Regional Real Revenue, General Allocation Fund, Specific Allocations Fund partially effect on Gross Regional Domestic Product of Central Sulawesi Propince 2010-2016 Period. The testing in this research was Multiple Linear Regression dataÂ  panel with coefficient Determination, F test, and t for all data were processed by using Eviews 7.0. The result of F test shows the Regional Real Revenue, General Allocation Fund, and Specific Allocation Fund, simultaneously affect the Gross Regional Domestic Product. It shows a larger F-count 56.06551> F- table of 0.05 where of the t test Result only Regional Real Income and the Specific Allocation Fund affecting the Gross Regional Bruto Product.